(untitled) (Third Sector Social Economic Review, 2025)
This study analyzes Türkiye’s sustainable development performance by examining temporal trends in agriculture- and environment-related Sustainable Development Goals (SDGs). Data covering the period from 2000 to 2023 were evaluated using graphical trend analysis and the Modified Mann-Kendall trend test. The findings reveal a statistically significant and positive trend in SDG 1 (No Poverty), while significant negative trends were identified in SDG 2 (Zero Hunger), SDG 12 (Responsible Consumption and Production), SDG 13 (Climate Action), and SDG 15 (Life on Land). These results highlight not only shortcomings in sectoral policies but also a lack of integration among the SDGs. While notable progress has been made in poverty reduction, the stagnation in hunger-related indicators points to a disconnection between food systems and social policy frameworks. Moreover, imbalances in production and consumption patterns hinder the achievement of environmental targets. The study emphasizes that sustainability can only be achieved through a long-term, integrated, and structural policy transformation.